Classification of Language Transmitting Families in Diglossic Contexts - Antón i Álvarez de Cienfuegos, Maria (2023)
Based on the qualitative study of diglossia in Northern Catalonia (France), this article presents a new classification of the families responsible for the transmission, since this linguistic practice has a strong impact on the situation of the languages in the territory. Thus, the aims of this paper are as follows: (1) to present the new classification of families in a diglossic situation, taking into account the linguistic choices in communication with descendants and among adults; (2) to define the main elements of the five types of families, as well as their specific applications and constraints in regards to the practices of interruption, continuity and revernacularization of a minority language; and finally, (3) to establish the transmission tendencies according to the typology of the family. As a result of this analysis, five typologies have been established and described so that they can provide theoretical underpinning for future sociolinguistic research focused on the study of families and on planning the revitalization of a minoritized language, whether indigenous or allochthonous.